Comparison Study of Hydration Characteristics Between Cements with 50% and 85% Slag - Junwei SONG; Lu WANG; Shuhua LIU; Jielu ZHU; Yong OUYANG (Medžiagotyra, 2018)
This study aims at comparing the hydration characteristics between two kinds of cements, the Portland slag cement (PSC) containing 50 wt.% ground granulated blast furnace slag (GGBFS), and the supersulfated cement (SSC) containing 85 wt.% GGBFS. The reason caused the different hydration properties with the same type raw materials were analyzed by determining the compressive strength of the pastes, the hydration heat release and the hydration products at different curing ages. The results show that in PSC system, alkali activation was predominating and it mainly generated hydrated calcium silicate (C-S-H gels) and calcium hydroxide (CH). While in SSC system, the hydration mechanism was the combination of sulfate and alkali excitation, it mainly generated C-S-H gels and ettringite. The compressive strength of PSC was higher than that of SSC at every curing age. However, the difference of the compressive strength between PSC and SSC narrowed gradually as curing age went on. The early compressive strength of PSC was high while at late hydration age it increased slowly. The early compressive strength of SSC was low, while the later compressive strength increased quikly. Compared with PSC, the hydration heat evolution rate of SSC was slower and the hydration heat of SSC was relatively less low. Moreover, the second exothermic peak of SSC delayed. DOI: http://dx.doi.org/10.5755/j01.ms.24.4.17746